Quasi-3D Geoelectrical Imaging as A New Application for Landslide Investigations: A Tunnel Case Induced by Blasting Activity - Cahyadi, Rudi; Widodo, Widodo (Jurusan Fisika FMIPA Universitas Andalas, 2024)
Landslides are a significant hazard in mountainous regions, especially when influenced by construction activities such as tunnel excavation. In this paper, we aim to conduct a slope stability analysis as a result of tunnel blasts using quasi-3D subsurface models based on resistivity values. The study site is a construction area for the Jakarta-Bandung High-Speed Train tunnel, located in a mountainous region undergoing drill-and-blast excavation. This excavation method makes the area susceptible to landslides, which pose a threat to settlements in the Padalarang subdistrict, West Bandung Regency, Indonesia. Data was collected along four lines in 2D, and the dipole-dipole array was used to enhance resolution. Data modeling was carried out using ResIPy v3.2.3 software to create 2D and quasi-3D subsurface models based on resistivity values. The study findings indicate that the study area exhibits three resistivity ranges: low resistivity (0-30 Ωm), medium resistivity (31-49 Ωm), and high resistivity (>50 Ωm). Utilizing quasi-3D imaging, we were able to identify the dimensions and presence of slip surfaces, which can be categorized as shallow (1.5-5 m) and deep (5-20 m) criteria. This study successfully applied the quasi-3D geoelectrical approach in a susceptible environment to detect potential landslide zones.